An association analysis for 14 candidate genes mapping to meat quality quantitative trait loci in a Duroc pig population reveals that the ATP1A2 genotype is highly associated with muscle electric conductivity. (21st October 2019) - Mármol‐Sánchez, E.; Quintanilla, R.; Jordana, J.; Amills, M.
Summary: In previous GWAS carried out in a Duroc commercial line (Lipgen population), we detected on pig chromosomes 3, 4 and 14 several QTL for gluteus medius muscle redness (GM a *), electric conductivity in the longissimus dorsi muscle (LD CE) and vaccenic acid content in the LD muscle (LD C18:1 n  − 7), respectively. We have genotyped, in the Lipgen population, 19 SNPs mapping to 14 genes located within these QTL. Subsequently, association analyses have been performed. After correction for multiple testing, two SNPs in the TGFBRAP1 (rs321173745) and SELENOI (rs330820437) genes were associated with GM a *, whereas ACADSB (rs81449951) and GPR26 (rs343087568) genotypes displayed significant associations with LD vaccenic content. Moreover, the polymorphisms located at the ATP1A2 (rs344748241), ATP8B2 (rs81382410) and CREB3L4 (rs321278469 and rs330133789) genes showed significant associations with LD CE. We made a second round of association analyses including the SNPs mentioned above as well as other SNPs located in the chromosomes to which they map. After performing a correction for multiple testing, the only association that remained significant at the chromosome‐wide level was that between the ATP1A2 genotype and LD CE. From a functional point of view, this association is meaningful because this locus encodes a subunit of the Na + /K + ‐ATPase responsible for maintaining an electrochemical gradient across the plasma membrane.